Analytical Statistics for the Situation of the Thai Elderly 2017 - 2022 - Voraprateep, Jutharath (Technium Social Sciences Journal, 2025)
The research objectives are (1) to analyze the situation of the Thai elderly from 2017 to 2022, using appropriate statistical analysis, and (2) to present the situation of the Thai elderly from 2017 to 2022 using descriptive and inferential statistics. In this research, the Thai elderly data from 2017 to 2022 in four dimensions: economic, environment, health, and social, from the Department of Older Persons (DOP), the Minister of Social Development and Human Security, is analyzed and presented. The research results were summarized as follows: 1. The number and percentage of the Thai elderly from 2017 to 2022 increased. 2. The report on the situation of the Thai elderly from 2017 to 2022 has different issues each year, for example, in 2017, there was active ageing, in 2018, there was Thai elderly work, in 2019, there was social welfare, and in 2020, there was on the impact of COVID-19, etc.